A new adaptive thermal comfort model for the Romanian climate. Issue 3 (28th August 2018) - Udrea, Ioana; Croitoru, Cristiana; Nastase, Ilinca; Crutescu, Ruxandra; Badescu, Viorel
Abstract : Adaptive thermal comfort refers to the ability that the occupants of a building have to accustom themselves to specific thermal conditions. The notion of human thermal comfort (HTC) is therefore introduced and defined by a simple mathematical equation. In the evaluation process of actual buildings and in the design of new ones, adaptive HTC equations translate into a substantial reduction in energy consumption and maintenance costs to the buildings. Specialised databases provide adaptive HTC equations that are regarded as standard over large geographical areas. However, in particular climate regions, new adaptive HTC equations have to be established. This paper aims to find an HTC equation specific to the Romanian climate (Köppen climate type D – temperate continental climate). In order to achieve that, a field survey was conducted between 2013 and 2014 in several naturally ventilated buildings (two university buildings from Bucharest, a passive office building and a residential house). The input data consist of questionnaire surveys as well as measurements of comfort parameters.